FACTORS CAUSING THE DECLINE IN CERAMIC WORKERS' PRODUCTIVITY AND STRATEGIES FOR IMPROVEMENT: FAKTOR PENYEBAB PENURUNAN PRODUKTIVITAS TUKANG KERAMIK DAN STRATEGI PENINGKATANNYA - Ferdy Kahandanie; Mahfud; Candra Irawan; Ferdy Novri (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
This study examines the comparison of labor productivity during normal working hours and overtime in the ceramic installation work of the Transit Office renovation project of the Ministry of Finance in Balikpapan City.The main issue is how the value of labor productivity differs between normal working hours and overtime, and its impact on the decline in productivity and the increase in wage costs.The research method was conducted through direct observation in the field over 10 days during normal working hours (08:00–16:00) and overtime hours (19:00–22:00), focusing on the productivity of ceramic workers using 60cmx60cm ceramic tiles.The research results show a significant difference in labor productivity between normal working hours and overtime, where productivity during overtime decreases due to fatigue, which also leads to an increase in labor wage costs.In conclusion, although overtime can accelerate project completion in the short term, the implementation of overtime hours in the long term negatively impacts productivity and cost efficiency. Therefore, proper management of overtime hours is necessary to maintain a balance between time, cost, and quality in construction projects.